Hubungan Tingkat Pengetahuan Tentang Hipertensi dengan Tindakan Pencegahan Hipertensi di BPSTW Budi Luhur Bantul - Irianti, Chindra H; Antara, Antok Nurwidi; Jati, Marius Agung Sasmita (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
Hypertension is an increase in systemic blood pressure persistent where the systolic blood pressure is ≥ 140 and the diastolic blood pressure ≥ 90 mmHg. Hypertension is one of the main causes of morbidity in increasing morbidity and mortality or mortality rates in Indonesia, so the management of this disease is a very common intervention conducted at various levels of health facilities. The aim of this research is to know the relationship level of knowledge about hypertension with hypertension prevention measures in the elderly at BPSTW Budi Luhur Bantul. The research design used a cross sectional approach, namely a research design in which the measurement or observation was carried out simultaneously at one time. The research design used in this research was purposive sampling, namely sampling for a specific purpose. The sample in this research were all hypertension patients in BPSTW Budi Luhur Bantul as many as 44 respondents. Based on the results of the Spearman Rank calculation, it was obtained p-value = 0.642> (0.05) (p-value greater than α = 0.05. This means that there is no significant relationship between the level of knowledge about hypertension and hypertension prevention measures in the elderly at BPSTW Budi Luhur Bantul. The conclusion is that there is no significant relationship between the level of knowledge about hypertension and hypertension prevention measures in the elderly at BPSTW Budi Luhur Bantul.